The Repo Code: A Study of Adjustment to Uncertainty in Commercial Law - Jean Braucher (Washington University Law Quarterly, 1997)
This Article challenges the conventional wisdom about the routine importance of certainty in commercial law through the exploration of one example-the law of self-help repossession.
Keywords: Collateral security; Breach of the peace